2017
DOI: 10.9746/jcmsi.10.495
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Control of Multi-Robot Systems: A Survey

Abstract: : Recently, significant gains have been made in our understanding of multi-robot systems, and such systems have been deployed in domains as diverse as precision agriculture, flexible manufacturing, environmental monitoring, search-and-rescue operations, and even swarming robotic toys. What has enabled these developments is a combination of technological advances in performance, price, and scale of the platforms themselves, and a new understanding of how the robots should be organized algorithmically. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(32 citation statements)
references
References 64 publications
0
31
0
1
Order By: Relevance
“…Robot i is in charge of surveiling only its Voronoi cell V i . As shown in [9], the cost to minimize in order to execute this surveillance task is given by…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robot i is in charge of surveiling only its Voronoi cell V i . As shown in [9], the cost to minimize in order to execute this surveillance task is given by…”
Section: Methodsmentioning
confidence: 99%
“…they can be broken down into the sum of pairwise costs among each robot i and its neighboring robots j ∈ N i . In [9], the authors illustrate the various multi-robot tasks represented by such a cost, and demonstrate the decentralized nature of the control law obtained by performing a gradientdescent on this cost. Furthermore, in [13], we showed that in this case, the constraint-based task execution can be rendered decentralized provided that certain conditions on the extended class K function gamma that appears in (14b) are satisfied.…”
Section: B Qp Relaxation For Heterogeneous Task Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Local, scalable, safe and emergent are four essential features that decentralized multi-robot coordinated control algorithms should possess [24]. Many algorithms that satisfy these properties have been developed for applications ranging from social behavior mimicking [25], formation assembling [26] and area patrolling [27].…”
Section: Constraint-based Control Of Multi-robot Systemsmentioning
confidence: 99%
“…Research on modeling, prediction and control of multiagent systems, e.g., teams of quadcopters, autonomous cars, or other forms of unmanned vehicles, has gained considerable attention in a variety of research disciplines. For an excellent recent survey of how such teams can be formalized, coordinated, and controlled, we refer the reader to [7]. Among the formalisms most widely used for representing and studying MRS and swarms are graphtheoretic [8] approaches and methods based on cost functions and auctioning processes [2].…”
Section: Related Workmentioning
confidence: 99%